Factors associated with unmet need for support to maintain independence in later life: a systematic review of quantitative and qualitative evidence. (28th October 2022) - Spiers, Gemma Frances; Kunonga, Tafadzwa Patience; Stow, Daniel; Hall, Alex; Kingston, Andrew; Williams, Oleta; Beyer, Fiona; Bower, Peter; Craig, Dawn; Todd, Chris; Hanratty, Barbara
Abstract: Background: populations are considered to have an 'unmet need' when they could benefit from, but do not get, the necessary support. Policy efforts to achieve equitable access to long-term care require an understanding of patterns of unmet need. A systematic review was conducted to identify factors associated with unmet need for support to maintain independence in later life. Methods: seven bibliographic databases and four non-bibliographic evidence sources were searched. Quantitative observational studies and qualitative systematic reviews were included if they reported factors associated with unmet need for support to maintain independence in populations aged 50+, in high-income countries. No limits to publication date were imposed. Studies were quality assessed and a narrative synthesis used, supported by forest plots to visualise data. Findings: forty-three quantitative studies and 10 qualitative systematic reviews were included. Evidence across multiple studies suggests that being male, younger age, living alone, having lower levels of income, poor self-rated health, more functional limitations and greater severity of depression were linked to unmet need. Other factors that were reported in single studies were also identified. In the qualitative reviews, care eligibility criteria, the quality, adequacy and absence of care, and cultural and language barriers were implicated in unmet need. Conclusions: this review identifies which groups of older people may be most at risk of not accessing the support they need to maintain independence. Ongoing monitoring of unmet need is critical to support policy efforts to achieve equal ageing and equitable access to care.